Application of trigonometry in physics - Нестеренко, Л.І.; Логвин, М.М.; Покидько, Л.М. (Proceedings of National Aviation University (archive), 2010)
In the article it is considered using of trigonometric functions and trigonometric transformations for the decision of tasks from physics. The use of trigonometric concepts is considered in the different spheres of human activity.